Comparison of Antioxidant Activity Tests Using the DPPH, ABTS, and FRAP Methods on Ethanol Extracts of Cherry Leaves (Muntingia calabura L.) and Total Flavonoids - Alya Atla Lidya; Anna Fitriawati; Bagas Ardiyantoro (CV. AFDIFAL MAJU BERKAH, 2025)
This study investigates the antioxidant activity of ethanol extracts of Muntingia calabura L. leaves using DPPH, ABTS, and FRAP methods. The background emphasizes increasing environmental pollution and free radical-induced oxidative stress, which contribute to degenerative diseases and aging. The research aims to compare the sensitivity and effectiveness of these three assays in evaluating the antioxidant potential of cherry leaves and to quantify their total flavonoid content. The study employs a comparative descriptive design with samples collected from Sukoharjo, Indonesia. Instruments used include spectrophotometers, rotary evaporators, and standard reagents. Data analysis involves IC50 calculation and statistical comparison of the methods. Results show that the ethanol extract exhibited high antioxidant activity with IC50 values below 50 μg/mL across all methods, with the highest sensitivity observed in the FRAP assay. The total flavonoid content was approximately 47.2 mgQE/g. The conclusion indicates that Muntingia calabura leaves possess potent antioxidant activity and high phenolic compounds, supporting their potential as natural antioxidant sources. Future research should explore different extraction techniques and in vivo assessments.